Haptoglobin Genotypic Polymorphisms and Longevity Among the Ghanaian Population in the Greater Accra Region - Nuwormegbe, S.A. (University of Ghana, 2013)
Background: Haptoglobin (Hp), an acute phase glycoprotein with antioxidant, anti-inflammatory and immune-modulatory functions may be an excellent candidate gene to investigate human longevity. Human Hp is polymorphic and these polymorphisms have been associated with different functional capacities of the proteins expressed as a result of their distinct biochemical and biophysical properties. Aim: To determine the possible role of haptoglobin genotypes as genetic markers for longevity. Methods: The study which was of cross-sectional design recruited 133 individuals aged 50 years and above. Blood samples were collected from participants for haematological analysis, haptoglobin genotyping by allele specific PCR and determination of oxidative stress by determining levels of reactive oxygen species by superoxide dismutase assay and oxidative DNA damage by comet assay. Results: A significant positive correlation between SOD activity and age in the study population (p-value of 0.002) was observed whiles a significant negative correlation was observed between age and total white blood cells, neutrophil and platelet counts (p-values of 0.020, 0.028 and 0.006 respectively). The HP1 and HP2 allelic frequencies were found to be 49.5 % and 50.5% respectively whiles the genotypic frequencies were 38%, 25% and 37% for HP 2-2, HP 2-1 and HP 1-1 respectively and showed a departure from the Hardy-Weinberg equilibrium. Comparison of the distribution of haptoglobin genotypes among age categories showed no significant association (p = 0.700). SOD activity in the study population was not significantly different when compared among the genotypes (p = 0.877). Extensive DNA damage/fragmentation was observed in the study population. The degree of damage among the genotypes however was similar. Conclusion: The HP1/2 genotypic polymorphisms did not influence longevity in the Ghanaian population and no genotype conferred a survival advantage.
Thesis (MPhil) - University of Ghana, 2013